Monetary Policy, Divergence, and the Euro - Moritz Pfeifer; Gunther Schnabl (CESifo GmbH, 2024)
This paper investigates the relationship between economic divergence and expansionary monetary policies within the eurozone based on a new divergence indicator. We study the dynamics between the economic divergence of member states and unconventional monetary policy in a Bayesian SVAR and find a strong positive response of the expansion of the ECB's balance sheet to rising divergence. We find weaker evidence for unconventional monetary policies lowering divergence. We interpret these findings as evidence that expansionary monetary policy aims to absorb shocks leading to divergence. However, it may exacerbate divergence and inflationary pressures in the long-run. This research contributes to the literature on Optimum Currency Areas (OCAs) by highlighting the dynamics between economic disparities and unconventional monetary policy.
Keywords: E52; E58; F15; F45; 330; optimum currency areas; unconventional monetary policy shocks; statistical identification